Sources of Conflict in the 21st Century : Regional Futures and U.S. Strategy - Edited By Khalilzad, Zalmay and Lesser, Ian O. (GHQ, Rawalpindi Army Education Press, 2001)
The problem of global, long-range defense planning has changed enormously since the end of the Cold War. The sources and types of conflict for which the military must plan have become more varied and less predictable, the range of potential adversaries is larger, the range of military missions is more diverse, and the nature of security itself is changing on a global basis. Defense analysts must begin to consider how many of today's leading adversaries will remain adversaries, if long-standing allies will change their orientation, who will be called on to intervene and where, and if we can expect stability or chaos. This book examines current political trends and potential sources of conflict in three critical regions--Asia, the greater Middle East, and Europe and the former Soviet Union--through the year 2025. The authors describe possible alternative strategic "worlds," including a projection of today's mixed political climate, a more benign world in which the great powers are at peace and are actively cooperative, and a world beset with economic, demographic, and political turmoil. Additional chapters discuss regional trends and their meaning for strategy and planning. Originally intended to serve Air Force long-range planning needs, the findings are relevant to broader ongoing debates and should be of interest to a wide foreign and security policy audience.
Include Maps and Tables
Keywords: Air defenses -- United States. -- United States